KERUKUNAN UMAT BERAGAMA DALAM PIKIRAN DAN PRAKTIK KELOMPOK KEAGAMAAN ISLAM DI JAYAPURA (Harmoni, 2020)
This research is intended to understand the perspective and practice of religious harmony among Islamic groups in City and Regency of Jayapura, Papua Province.The perspective and practice of harmony is placed in a social, cultural, political, and economic context.Research using qualitative approaches, interviews and observations became the main instruments in research.The results showed the Perspective of Islamic groups towards religious harmony was built through the process of meeting interactions in plural social spaces and intensive interactions to positive effects by Muslims to other religions, especially Christians.The principle of daasar that builds the perspective of religious harmony from Islamic groups is the principle of moderation and inclusion of Islam in building interactions with adherents of other religions that conform to the vision of Islam as rahmatan lil alamin religion.The practice of religious harmony displayed by Islamist groups in Jayapura is a reflection of their moderate vision of Islam in the form of an active tolerance through intensive dialogue and cooperation especially in religious celebrations.
Keywords: Concord .Religious People, Islamic Groups, Socio-religious interactions